2017
DOI: 10.1007/s13205-017-0670-4
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver oxide nanoparticles and its antibacterial activity against dental pathogens

Abstract: In the present study, the use of silver oxide nanoparticles (AgO NPs) synthesized using Ficus benghalensis prop root extract (FBPRE) as a reducing and stabilizing agent is reported and evaluated for its antibacterial activity against dental bacterial strains. The effects of pH, extract concentration, metal ion concentration, and contact time were studied to confirm the optimum production of AgO NPs. Our results suggest that, by increasing the extract concentration and the time frame, there will be a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(60 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…Different research studies have reported the green synthesis of different MNPs using aqueous and ethanolic extracts (Esfanddarani, Kajani, & Bordbar, 2017;Fatimah, Pradita, & Nurfalinda, 2016;Vélez et al, 2018). Up till now, limited comparative studies with regard to synthesis, characterization, and different biological applications of Ag 2 ONPs have been performed using plant extracts of C. lanceolatus (Ravichandran et al, 2016) and Ficus benghalensis (Manikandan et al, 2017). The presence of green chemicals (herbacetin, rhamnocitrin, physcion, kaempferol, maesopsin, quercetin, and emodin) in R. virgata has necessitated it to be used in However, no blue/red shift was observed in the peak position, and therefore we attribute/assume the stable SPR behavior of NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Different research studies have reported the green synthesis of different MNPs using aqueous and ethanolic extracts (Esfanddarani, Kajani, & Bordbar, 2017;Fatimah, Pradita, & Nurfalinda, 2016;Vélez et al, 2018). Up till now, limited comparative studies with regard to synthesis, characterization, and different biological applications of Ag 2 ONPs have been performed using plant extracts of C. lanceolatus (Ravichandran et al, 2016) and Ficus benghalensis (Manikandan et al, 2017). The presence of green chemicals (herbacetin, rhamnocitrin, physcion, kaempferol, maesopsin, quercetin, and emodin) in R. virgata has necessitated it to be used in However, no blue/red shift was observed in the peak position, and therefore we attribute/assume the stable SPR behavior of NPs.…”
Section: Resultsmentioning
confidence: 99%
“…AgNPs were also used in various fields of dentistry, such as dental prostheses, restorative and endodontic dentistry, and implantology [ 147 ]. Thanks to their unique properties feasible for different domains of real interest in modern society, silver nanoparticles hold a prominent place in nanomaterial-related restorative, regenerative, and multifunctional biomedicine [ 148 , 149 ].…”
Section: Silver Nanoparticles For Dental Applicationsmentioning
confidence: 99%
“…[ 4 , 5 ], Streptococcus spp. [ 113 , 124 ], and Bacillus spp. [ 114 , 120 ], and gram-negative bacteria such as Escherichia spp.…”
Section: Bactericidal Properties and Synergistic Enhancement Of Comentioning
confidence: 99%